The complete chloroplast genome of Sisymbrium irio. Issue 2 (3rd July 2018) - Kawanabe, Takahiro; Nukii, Hiroaki; Furihata, Hazuka Y.; Yoshida, Takanori; Kawabe, Akira
Abstract: The complete chloroplast genome of Sisymbrium irio was determined. The length of the complete chloroplast genome is 154, 001 bp. The whole chloroplast genome consists of 83, 891 bp long single copy (LSC) and 17, 630 bp small single copy (SSC) regions, separated by a pair of 26, 240 bp inverted repeat (IR) regions. The S. irio chloroplast genome encodes 112 annotated known unique genes including 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. The phylogenetic position of S. irio is sister to Brassiceae and Thlaspideae.